Peningkatan penguasaan mufradat bahasa arab melalui penggunaan quiz game model cerdas cermat - Muhamad Nazil Furqon; Dede Rizal Munir (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study is a Classroom Action Research (CAR) aimed at improving students’ mastery of Arabic vocabulary (mufradāt) through the implementation of a quiz game in the form of a “quiz bowl” (cerdas cermat) for tenth-grade students of class X at MA MAI Purwakarta. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study were 16 students with a Minimum Mastery Criterion (KKM) of 70. The results showed an improvement in students’ vocabulary mastery. In cycle I, the average score was 70.63 with a classical mastery of 75%. In cycle II, the average increased to 80.94 with a classical mastery of 100%. Therefore, it can be concluded that the use of the quiz game cerdas cermat is effective in improving the Arabic vocabulary mastery of students in class X MA MAI Purwakarta.